THE FEATURES OF WOMEN’S LANGUAGE SPOKEN BY THE FEMALE CHARACTERS IN RAYA AND THE LAST DRAGON MOVIE - Lestari, Ni Putu Lia Cahya; Saientisna, Made Detriasmita; Maharani, Sang Ayu Isnu (Jurnal Review Pendidikan dan Pengajaran, 2024)
The research entitled The Features of Women’s Language Spoken by the Female Characters in Raya and The Last Dragon Movie. It aims to identify the type of women’s language features based on Lakoff's (2004) theory and the social context based on Holmes's (2013) theory. This research studied and reviewed some studies related to women’s language. This research was conducted by using a descriptive qualitative method, for collecting the data was watched the movie several times, read subtitles of the movie, and selected the female character’s utterances that contain the women’s language features. As a result, there are found 63 data women’s language features in this movie. There were seven types of women’s language features found in this movie. There were lexical hedges or fillers, tag questions, intensifiers, rising intonation, empty adjectives, super polite forms, and emphatic stress. Based on the findings of type of women’s language features, there were social contexts such as the participants, the participants in this movie are Sisu, Raya, Boun, Namaari, Dang Hu, Tong, Virana, and Benja. The setting, this movie mostly takes place while sailing in the ocean on a boat. The topics, the topic discussed are mostly about gems and how to save the world from druun and the function.